Etos Kerja Etnis India dan Pengaruhnya terhadap Komitmen Organisasi dengan Kepuasan Kerja sebagai Pemediasinya - Ananda Fitriani Dewi; Arasy Ayu Setiamy; Ninsin Cemarlian Lase (Universitas Harapan Medan, 2022)
The purpose of this study was to determine the effect of Indian ethnic work ethic on job satisfaction, to determine the indirect effect of Indian ethnic work ethic through job satisfaction on organizational commitment and to determine the effect of Indian ethnic work ethic directly on organizational commitment. This type of research is associative research. The population in this study is the number of employees of the Medan Gursiwara Mission, amounting to 100 people and the sample used in this study is 100 people using boring samples. Data analysis technique in this research is path analysis. The results showed that the ethnic work ethic of India had a significant and significant effect on employee job satisfaction. Job satisfaction does not significantly influence organizational commitment. There is no direct effect between Indian ethnic work ethics on organizational commitment through employee job satisfaction